2018
DOI: 10.1590/1414-431x20187427
|View full text |Cite
|
Sign up to set email alerts
|

Study of major genetic factors involved in pituitary tumorigenesis and their impact on clinical and biological characteristics of sporadic somatotropinomas and non-functioning pituitary adenomas

Abstract: Genetic and functional aberrations of guanine nucleotide-binding protein, alpha stimulating (GNAS), aryl hydrocarbon receptor interacting protein (AIP), and pituitary tumor transforming gene (PTTG) are among the most prominent events in pituitary tumorigenesis. A cohort of Brazilian patients with somatotropinomas (n=41) and non-functioning pituitary adenomas (NFPA, n=21) from a single tertiary-referral center were evaluated for GNAS and AIP mutations and gene expression of AIP and PTTG. Results were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…3 ). GNAS -mutated tumors are smaller ( 145–149 ), less likely to be locally invasive ( 149 ), and more likely to respond to SSAs ( 149 , 150 ), although a Brazilian cohort showed no differences in tumor extension or response to SSAs between mutated and nonmutated tumors ( 151 ). Dopamine receptor 2 expression is increased in GNAS -mutated tumors, potentially allowing for GNAS mutation status in predicting the response to dopamine agonists in GH-PTs ( 17 ).…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…3 ). GNAS -mutated tumors are smaller ( 145–149 ), less likely to be locally invasive ( 149 ), and more likely to respond to SSAs ( 149 , 150 ), although a Brazilian cohort showed no differences in tumor extension or response to SSAs between mutated and nonmutated tumors ( 151 ). Dopamine receptor 2 expression is increased in GNAS -mutated tumors, potentially allowing for GNAS mutation status in predicting the response to dopamine agonists in GH-PTs ( 17 ).…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Knosp grade, Knosp modification and Hardy–Wilson classifications are widely used and offer a good orientation. The Knosp grade offers the greatest diagnostic accuracy for the prediction of a surgical cure [ 40 , 41 , 42 ]. In addition, the degrees of ICA contact and Knosp score are associated with postoperative endocrine outcomes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent a multiomic analysis of a GNAS locus in two independent somatotroph tumor cohorts revealed that 43% of gsp-negative tumors showed a GNAS imprinting relaxation, which corresponded to a lower GNAS, SSTR2 and AIP expression, and a lower sensitivity to SSAs and potentially aggressive behavior [42]. However, the Oxford cohort showed that the granulation pattern in a tumor subtype, not the gsp mutation, predicts the tumor response to the SSAs while a Brazilian cohort showed no difference between the tumors with or without a GNAS mutation [39,43]. To conclude, even though the prevailing opinion is that the GNAS mutation is an indicator of a better response to the treatment, there are studies with controversial results.…”
Section: Gnas Mutationsmentioning
confidence: 95%